The impact of political treaties and domestic and regional events on wood trade (A case study of Iran, Russia and the Warsaw Pact countries) - Marzeyeh Abasi (Regional Information Center for Science and Technology (RICeST), 2018)
International trade has a significant share of the global economy; the issue of regulating foreign economic relations is a major contributor to political talks in the countries. Social, political and cultural events, including political and economic agreements, have a tremendous impact on the trade of countries. Forests around the world produce large amounts of wood and trade in products throughout the world. Since Iran has been trading in wood with Russia and other European countries about 100 years ago, this study was aimed at investigating the effects of political events on the bilateral exports of timber in Iran and Russia, as well as the effect of the Warsaw Treaty and its collapse on The wood trade of member countries with Iran was done using the gravity pattern. The results of the study show that the Warsaw Pact as a political treaty affects the trade relations of the countries of the covenant with Iran, and the per capita income of two trade partners, exchange rate changes and geographical distances on the volume of wood trade and Wood products have been effective. Results for both Iran and Russia show the impact of wood trade on political events as well as domestic laws and bills approved by the two countries.